An adjuvanted chimeric spike antigen boosts lung-resident memory T-cells and induces pan-sarbecovirus protective immunity - Claudio Counoupas; Elizabeth Chan; Paco Pino; Joshua Armitano; Matt D. Johansen; Lachlan J. Smith; Caroline L. Ashley; Eva Estapé; Jean Troyon; Sibel Alca; Stefan Miemczyk; Nicole G. Hansbro; et al. (npj Vaccines)
Abstract Next-generation vaccines are essential to address the evolving nature of SARS-CoV-2 and to protect against emerging pandemic threats from other coronaviruses. These vaccines should elicit broad protection, provide long-lasting immunity and ensure equitable access for all populations. In this study, we developed a panel of chimeric, full-length spike antigens incorporating mutations from previous, circulating and predicted SARS-CoV-2 variants. The lead candidate (CoVEXS5) was produced through a high-yield production process in stable CHO cells achieving >95% purity, demonstrated long-term stability and elicited broadly cross-reactive neutralising antibodies when delivered to mice in a squalene emulsion adjuvant (Sepivac SWE™). In both mice and hamsters, CoVEXS5 immunisation reduced clinical disease signs, lung inflammation and organ viral titres after SARS-CoV-2 infection, including following challenge with the highly immunoevasive Omicron XBB.1.5 subvariant. In mice previously primed with a licenced mRNA vaccine (Comirnaty XBB.1.5, termed mRNA-XBB), CoVEXS5 boosting significantly increased neutralising antibody (nAb) levels against viruses from three sarbecoviruses clades. Boosting with CoVEXS5 via systemic delivery elicited CD4+ lung-resident memory T cells, typically associated with mucosal immunisation strategies, which were not detected following mRNA-XBB boosting. Vaccination of hamsters with CoVEXS5 conferred significant protection against weight loss after SARS-CoV-1 challenge, compared to mRNA-XBB immunisation, that correlated with anti-SARS-CoV-1 nAbs in the sera of vaccinated animals. These findings highlight the potential of a chimeric spike antigen, formulated in an open-access adjuvant, as a next-generation vaccine candidate to enhance cross-protection against emerging sarbecoviruses in vaccinated populations globally.